Factors associated with quality of life in Chinese people with psoriasis: a cross-sectional study - Xiu-jie Zhang; Jing-rong Lin; Min-xing Ou; Hong-wei Yan; Sheng-nan Liu; Lu Dai; Fu-qing Gong (BMC, 2023)
Abstract Background The ultimate goal of medical care is to eradicate disease and restore normality to a person's life. Quality of life (QOL) is a concern as dermatologists and researchers strive to find better drug treatments. However, there have been few reports on the factors associated with QOL among Chinese people with psoriasis. Methods A total of 185 people with psoriasis were surveyed to assess their sociodemographic status, disease-related information, psychosocial status, and QOL. The questionnaires included a sociodemographic questionnaire, the Athens Insomnia Scale, the Hospital Anxiety and Depression Scale, the Perceived Social Support Scale, the Psychosocial Adaptation Questionnaire of Chronic Skin Disease and the Dermatology Life Quality Index. Multiple stepwise regression and path analysis were used to study the factors associated with QOL among Chinese people with psoriasis and to analyse the relationship between them. Results The results showed that the presence of anxiety/depression, lesion area, sleep disorders, psychosocial adaptation, and sex could jointly predict 62.1% of the variance in QOL among Chinese people with psoriasis. According to previous theories and the literature, a path model was established for five variables. Four internal variables could be effectively explained. The values of the explanatory variables were 62.1% (F(1056) = 61.020, p = 0.000) for QOL, 71.8% (F(2433) = 117.370, p = 0.000) for anxiety/depression, 44.0% (F(660) = 36.935, p = 0.000) for sleep disorders, and 66.9% (F(6886) = 93.556, p = 0.000) for psychosocial adaptation. The path analysis confirmed that 9 paths were consistent with the predicted path, and 3 paths were not confirmed. Conclusion To improve QOL among Chinese people with psoriasis, attention should be given to the presence of anxiety/depression, lesion area, sleep disorders, psychosocial adaptation and sex differences. Therefore, health care programs for psoriasis should include physical, psychological and social aspects.